Development of Augmented Reality Based Applications to Improve Students' High Order Thinking Skills in Acid Base - Sri Adelila Sari; Annisa Fitri; Hanisah Hasibuan (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study aimed to develop mobile application-based learning media with Augmented Reality (AR) technology on acid-base material to improve students' high order thinking ability (HOTS). AR is a technology that combines virtual objects into the real world interactively and in real-time, helping to visualize abstract chemical concepts. The method used is a 4-D model development research (Define, Design, Develop, Disseminate). The validation results showed that the media was very valid with a score of 82.4% for material experts, 93% for media experts, and 90.4% for chemistry teachers. The practicality of the media based on student questionnaires reached 90.70% (very practical category). The effectiveness of the media was proven through a one-sample t-test hypothesis test with a tcount value = 2.436 > ttable = 2.040 at α = 0.05, so that H₀ was rejected and Hₐ was accepted. This showed that student learning outcomes were higher than the KKM value (77), with an N-Gain score of 0.7162 (high category). Thus, this AR-based learning media was valid, practical, and effective for chemistry learning. The implications of this study indicate that the use of AR technology in chemistry learning is an innovative solution effective in improving students' understanding and HOTS.